THE ANALYSIS OF SERVICE QUALITY AND BRAND IMAGE TOWARDS DECISIONS TO ENROLL AND ITS IMPLICATIONS ON CONSUMER SATISFACTION OF THE BERINGIN PRATAMA FOOTBALL SCHOOL BEKASI - Al Muthiya, Jundi; Sitio, Arifin (Dinasti Publisher, 2021)
The purpose of this research is to analyze the effect of service quality and brand image towards consumer satisfaction, as well as to determine the role of the decision to enroll as a mediating variable that affects service quality and brand image towards consumer satisfaction at the Beringin Pratama Football School Bekasi. The population in this research was all 130 students at the Beringin Pratama Football School Bekasi in 2020. The sample employed in this research was 100 respondents. The sampling method was carried out by a stratified random sampling method. In addition, this research employed the path analysis data analysis technique. Finally, this research indicated some following results, namely: service quality had positive and significant effects on the decision to enroll, the brand image had positive and significant effects on the decision to enroll, service quality had positive and significant effects on consumer satisfaction, and brand image had positive and significant effects on consumer satisfaction. Nonetheless, the decision to enroll was not proven to have positive and significant effects on consumer satisfaction.